Distribution of the native strain in human alpha(1)-antitrypsin and its association with protease inhibitor function - Seo, EJ; Im, H; Maeng, JS; Kim, KE; Yu, MH (AMER SOC BIOCHEMISTRY MOLECULAR BIOLOGY INC, 2000)
Serine protease inhibitors (serpins) are metastable in their native state. This strain, which is released upon binding to target proteases, is essential for the inhibitory activity of serpins. To understand the structural basis of the native strain, we previously characterized stabilizing mutations of alpha(1)-antitrypsin, a prototypical inhibitory serpin, in regions such as the hydrophobic core. The present study evaluates the effects of single point mutations throughout the molecule on stability and protease inhibitory activity. We identified stabilizing mutations in most secondary structures, suggesting that the native strain is distributed throughout the molecule. Examination of the substitution patterns and the structures of the mutation sites revealed surface hydrophobic pockets as a component of the native strain in alpha(1)-antitrypsin, in addition to the previously identified unusual interactions such as side chain overpacking and cavities. Interestingly, many of the stabilizing substitutions did not affect the inhibitory activity significantly. Those that affected the activity were confined in the regions that are mobilized during the complex formation with a target enzyme. The results of our study should be useful for designing proteins with strain and for regulating the stability and functions of serpins.
Keywords: REACTIVE CENTER LOOP; HUMAN ALPHA-1-PROTEINASE INHIBITOR; PLASMINOGEN-ACTIVATOR INHIBITOR-1; PROTEINASE-INHIBITORS; SUICIDE SUBSTRATE; CRYSTAL-STRUCTURE; HINGE REGION; SERPIN; MECHANISM; INSERTION